Variable densification of reduced graphene oxide foam into multifunctional high-performance graphene paper. Issue 45 (5th November 2018) - Xu, Fan; Chen, Ruofan; Lin, Zaishan; Sun, Xianxian; Wang, Shasha; Yin, Weilong; Peng, Qingyu; Li, Yibin; He, Xiaodong
Abstract : Our new strategy is very promising in terms of controlling the thickness, density, and size of graphene paper. Abstract : Super-flexible, electrically and thermally conductive graphene-based papers are in great demand in the fields of electronics and supercapacitors. However, the applications of graphene-based papers are limited either by their brittleness, small scale, or by their unsatisfactory thermal conductivity. Conventionally, such papers are fabricated by vacuum-assisted filtration, direct evaporation, electrospray coating, or wet spinning. Here we propose a novel strategy, namely, direct densification of reduced graphene oxide foam, to fabricate large-scale multifunctional graphene papers. The graphene paper density could be adjusted by applying different loads. The densities of the graphene papers varied from 0.32 g cm −3 to 1.85 g cm −3 . The thermal conductivity, tensile stress, electrical conductivity and electromagnetic interface shielding effectiveness increased with an increase in the density of the graphene paper. When the density of the graphene paper reached 1.85 g cm −3, the tensile stress was up to 50.4 MPa with strain of 4%, the thermal conductivity was 1103 W m −1 K −1 at room temperature and there was high electrical conductivity of 1.1 × 10 5 S m −1, as well as an electromagnetic interference (EMI) shielding effectiveness of 77.2 dB. Our new strategy is very promising in terms of controlling the thickness, density, and size of graphene paper. Our graphene paper has very high potential for applications.